Academic and Social Integration Experiences of Papuan Studying in University Students in Java - Cahya Wulandari; Shelley McKeown Jones (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Following the Special Autonomy Law in 2001, the number of Papuan students studying out of town soared, resulting integration into a new culture becomes inevitable. The authors were interested in exploring academic and social integration experiences amongst Papuan university students in Java. Semi-structured interview was used to collect data from six Papuan students (four males and two females). Data was analyzed using thematic analysis to identify factors influencing integration strategy and to explore how stereotypes affect the minority student’s acculturation strategy. These factors included the student’s personality traits and motivation, prior contact with outgroup members, support from the university, academic barriers, and language/communication barriers. Additionally, the study found that negative stereotypes were more commonly experienced by indigenous Papuan students compared to mixed-Papuan students. This suggests that cultural background of the students may play a role in their integration experiences. While the sample size of this study was small and may not be representative of the broader population, the findings provide important implications for educational institutions. The study highlights the importance of involving ethnic minorities in shaping educational policies related to integration. By addressing the factors identified in this study, educational institutions can create a more positive environment for all students.